Memantine monotherapy for Alzheimer's disease: a systematic review and meta-analysis. - Shinji Matsunaga; Taro Kishi; Nakao Iwata (PLoS ONE, 2015)
Background We performed an updated meta-analysis of randomized placebo-controlled trials testing memantine monotherapy for patients with Alzheimer's disease (AD). Methods The meta-analysis included randomized controlled trials of memantine monotherapy for AD, omitting those in which patients were also administered a cholinesterase inhibitor. Cognitive function, activities of daily living, behavioral disturbances, global function, stage of dementia, drug discontinuation rate, and individual side effects were compared between memantine monotherapy and placebo groups. The primary outcomes were cognitive function and behavioral disturbances; the others were secondary outcomes. Results Nine studies including 2433 patients that met the study's inclusion criteria were identified. Memantine monotherapy significantly improved cognitive function [standardized mean difference (SMD)=-0.27, 95% confidence interval (CI)=-0.39 to -0.14, p=0.0001], behavioral disturbances (SMD=-0.12, 95% CI=-0.22 to -0.01, p=0.03), activities of daily living (SMD=-0.09, 95% CI=-0.19 to -0.00, p=0.05), global function assessment (SMD=-0.18, 95% CI=-0.27 to -0.09, p=0.0001), and stage of dementia (SMD=-0.23, 95% CI=-0.33 to -0.12, p=0.0001) scores. Memantine was superior to placebo in terms of discontinuation because of inefficacy [risk ratio (RR)=0.36, 95% CI=0.17¬ to 0.74, p=0.006, number needed to harm (NNH)=non significant]. Moreover, memantine was associated with less agitation compared with placebo (RR=0.68, 95% CI=0.49 to 0.94, p=0.02, NNH=non significant). There were no significant differences in the rate of discontinuation because of all causes, all adverse events, and individual side effects other than agitation between the memantine monotherapy and placebo groups. Conclusions Memantine monotherapy improved cognition, behavior, activities of daily living, global function, and stage of dementia and was well-tolerated by AD patients. However, the effect size in terms of efficacy outcomes was small and thus there is limited evidence of clinical benefit.